Seascape genetics of the spiny lobster Panulirus homarus in the Western Indian Ocean: Understanding how oceanographic features shape the genetic structure of species with high larval dispersal potential. Issue 23 (16th November 2018) - Singh, Sohana P.; Groeneveld, Johan C.; Hart‐Davis, Michael G.; Backeberg, Björn C.; Willows‐Munro, Sandi
Abstract: This study examines the fine‐scale population genetic structure and phylogeography of the spiny lobster Panulirus homarus in the Western Indian Ocean. A seascape genetics approach was used to relate the observed genetic structure based on 21 microsatellite loci to ocean circulation patterns, and to determine the influence of latitude, sea surface temperature (SST), and ocean turbidity (KD490) on population‐level processes. At a geospatial level, the genetic clusters recovered corresponded to three putative subspecies, P. h. rubellus from the SW Indian Ocean, P. h. megasculptus from the NW Indian Ocean, and P. h. homarus from the tropical region in‐between. Virtual passive Lagrangian particles advected using satellite‐derived ocean surface currents were used to simulate larval dispersal. In the SW Indian Ocean, the dispersion of particles tracked over a 4‐month period provided insight into a steep genetic gradient observed at the Delagoa Bight, which separates P. h. rubellus and P. h. homarus . South of the contact zone, particles were advected southwestwards by prevailing boundary currents or were retained in nearshore eddies close to release locations. Some particles released in southeast Madagascar dispersed across the Mozambique Channel and reached the African shelf. Dispersal was characterized by high seasonal and inter‐annual variability, and a large proportion of particles were dispersed far offshore and presumably lost. In the NW Indian Ocean, particles were retained within the Arabian Sea. Larval retention and self‐recruitment in the Arabian Sea could explain the recent genetic divergence between P. h. megasculptus and P. h. homarus . Geographic distance and minimum SST were significantly associated with genetic differentiation in multivariate analysis, suggesting that larval tolerance to SST plays a role in shaping the population structure of P. homarus . Abstract : We examined the finer‐scale population genetic structure and phylogeography of the spiny lobster Panulirus homarus in the Western Indian Ocean. A seascape genetics approach was used to relate the observed genetic structure (21 microsatellite loci) to ocean circulation patterns, to determine the influence of latitude, sea surface temperature (SST), and ocean productivity (chl‐a) on population‐level processes. Genetic clusters correspond to three putative subspecies, P. h. rubellus from the SW Indian Ocean, P. h. megasculptus from the NW Indian Ocean, and P. h. homarus from the tropical region in‐between. Oceanography, latitude, and sea surface temperature were significantly associated with genetic differentiation between the three subspecies.